Position statement of the Brazilian Academy of Rhinology on the use of antihistamines, antileukotrienes, and oral corticosteroids in the treatment of inflammatory sinonasal diseases - Mion,Olavo de Godoy (2017)
Abstract Introduction: Inflammatory conditions of the nose and paranasal sinuses are very prevalent in the general population, resulting in marked loss of quality of life in affected patients, as well as significant work, leisure, and social activity losses. These patients require specific and specialized treatment. A wide range of oral medications are available. Objective: The present document is aimed to clarify, for professionals treating patients with inflammatory sinonasal diseases, both specialists and general practitioners, specific oral therapies in noninfectious nasal inflammatory conditions. Methods: The methodology used to create this article included the search for the key words: oral corticosteroids, antihistamines, antileukotrienes, rhinitis, rhinosinusitis in the MEDLINE and EMBASE databases in the last 5 years. Since no relevant article was found for the text on the subject of interest in the last 5 years, the search was extended for another 5 years, and so on, according to the authors’ needs. Results: Relevant literature was found regarding the use of antihistamines, antileukotrienes and oral corticosteroids in these conditions. The Brazilian Academy of Rhinology emphasizes, after extensive discussion by the collegiate, key points in the treatment with these drugs. Conclusion: There is support in the literature for the use of these drugs; however, final considerations about the role of each of them have been made.